Measurement of Radioactive Levels of 137Cs in Environmental Aerosols in Beijing - Rui-lin GAN; Juan DU; Lu LIU; Peng GAO; Xiu-feng MA (He huaxue yu fangshe huaxue)
With the development of nuclear energy and nuclear technology utilization in China, radiochemical analysis plays an important role in environmental quality monitoring, radiation environment monitoring around nuclear facilities, and emergency monitoring of nuclear and radiation accidents. 137Cs are typical artificial radioactive nuclides, mainly produced by global atmospheric nuclear testing, nuclear accidents, and nuclear technology applications. After entering the human body through the food chain, it will be evenly distributed throughout the body, causing internal irradiation. Therefore, monitoring the radioactive levels of 137Cs in environmental media is of great significance. There are two main methods for measuring 137Cs in aerosols: gamma spectrometer methods and radiochemical analysis. Due to the detection limit of gamma spectrometer methods is high, suitable for high activity samples, while the detection limit of radiochemical analysis is low, suitable for most environmental samples. In order to obtain more accurate results, this article used radiochemical analysis to pretreat environmental aerosol samples in Beijing. By analyzing and comparing samples at the same location using two pre-processing methods, it was found that 210Bi in the samples has a significant impact beta counting rate, resulting in higher measurement results. After ashing and leaching the sample, the isotopic carrier was added to remove 210Bi using co-precipitation method, and the pretreatment process was optimized. Gamma-ray spectrometry method was used to compare with the radiochemical analysis method to verify its reliability. It can be seen that the results are satisfactory in an experimental condition. Then, measurement of the radioactive levels of 137Cs in environmental aerosols in Beijing was conducted by radiochemical analysis method. The analysis results show that the activity concentration level of 137Cs in environmental aerosols in Beijing from 2016 to 2023 is (0.477±0.098)-(7.05±0.14) μBq/m3, whose average values is (1.46±1.26) μBq/m3. The monitoring results of environmental aerosols in Beijing are within the normal range of national aerosol monitoring results. In addition, based on the monitoring results and meteorological data analysis, dust weather can lead to an increase in the concentration of solid particles in the atmosphere, which in turn elevates the activity concentration of 137Cs in aerosols. Moving forward, it would be advisable to conduct long-term monitoring and further investigate the correlation between dust weather events and the activity concentration of 137Cs in environmental aerosols.